2017
DOI: 10.3389/fneur.2017.00432
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Voice Response to a Levodopa Challenge in Late-Stage Parkinson’s Disease

Abstract: BackgroundParkinson’s disease (PD) patients are affected by hypokinetic dysarthria, characterized by hypophonia and dysprosody, which worsens with disease progression. Levodopa’s (l-dopa) effect on quality of speech is inconclusive; no data are currently available for late-stage PD (LSPD).ObjectiveTo assess the modifications of speech and voice in LSPD following an acute l-dopa challenge.MethodLSPD patients [Schwab and England score <50/Hoehn and Yahr stage >3 (MED ON)] performed several vocal tasks before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 34 publications
(58 reference statements)
9
52
0
1
Order By: Relevance
“…For example, PD affects voice and speech in up to 90% of patients [16], compromising health, employment, social engagement, and quality of life [17, 18, 19]. These voice and speech deficits are mostly refractory to standard of care medical treatment (levodopa) [20] or surgical treatment (deep brain stimulation) [21, 22]. Although voice and speech changes are not commonly reported by patients with PD until the later stages of the disease [23], there is recent evidence of preclinical communication changes, both in humans [3] and in animal models [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PD affects voice and speech in up to 90% of patients [16], compromising health, employment, social engagement, and quality of life [17, 18, 19]. These voice and speech deficits are mostly refractory to standard of care medical treatment (levodopa) [20] or surgical treatment (deep brain stimulation) [21, 22]. Although voice and speech changes are not commonly reported by patients with PD until the later stages of the disease [23], there is recent evidence of preclinical communication changes, both in humans [3] and in animal models [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Among those articles, we found that Okada et al [25], analyzed isolated vowel articulation in PD subjects reporting that vowel space area was significantly expanded after L-DOPA treatment contrary to previous findings by [26], where no changes in speech over L-DOPA cycle were found. A recent article [27] analyzes a small cohort of late stage PD subjects using data from a L-DOPA challenge described in [28]. This work, which was limited to the analysis of sustained vowel /a/ and the repetition of a 8-word simple sentence, did not find significant changes in speech.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although voice disorders may be the primary concern regarding speech production in the early stages of the disease, disfluency and articulation impairments also emerge as the neurodegeneration progresses, with motor control deficits affecting articulation exerting the greatest negative impact on communication in the final stage of the disease. 10 Physiologically, hypokinetic dysarthria is associated with poor breath support and reduced range of motion of the speech articulators, 12,13 contributing to perceived undershoot of target sounds. 14 These acoustic-perceptual and physiological characteristics, therefore, have a detrimental effect on the individuals' intelligibility and, hence, their ability to communicate effectively.…”
Section: Hypokinetic Dysarthria Due To Pdmentioning
confidence: 99%
“…26 A recent study of levodopa effects on speech and voice in 24 individuals in the late stage of the disease (ie, with a Schwab and England score of <50 or a Hoehn and Yahr stage >3 while on medication) found no improvements in speech in response to this medication. 12 Thus, current evidence suggests limited and variable success in response to pharmacological treatment of dysarthria, leading to clinical reliance primarily on behavioral management strategies.…”
Section: Hypokinetic Dysarthria Due To Pdmentioning
confidence: 99%